ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNA E-WALLET DANA di BANGKALAN - Nova Auliatul Faizah; Aulia Dawam (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the influence of risk perception, information exposure, and trust on the interest of DANA e-wallet users in Bangkalan Regency. This study uses a quantitative-descriptive deductive method. This method is used to provide an overview of the characteristics and relationships between variables of DANA e-wallet users in Bangkalan. Through field data collection and statistical analysis, this approach systematically tests theory-based hypotheses to produce accurate and objective evidence of the phenomenon. The population in this study was DANA app users in Bangkalan whose exact number is unknown. Sampling was carried out using a non-probability sampling technique with a purposive sampling method, resulting in a sample of 96 respondents based on the Lemeshow formula calculation. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression analysis methods through the T test (partial) and F test (simultaneous). The results showed that partially, risk perception, information exposure, and trust had a positive and significant effect on user interest, with trust as the most dominant factor. Simultaneously, these three variables also had a positive and significant impact on user interest.